Organoleptic, physical, and chemical tests of artificial feed for milk fish substituted by earthworm meal (Lumbricus sp.) - Aslamyah, Siti; Karim, Muh. Yusri (Jurnal Akuakultur Indonesia, 2012)
﻿Earthworms meal (Lumbricus sp.) is very prospective as milkfish feed raw materials to substitute fish meal. Type of raw material and the exact composition will generate artificial feed quality with high levels of water stability, desirable, and safe for the fish. The purpose of this study to evaluate the quality of milkfish feed at different levels of fish meal substitution with earthworms (Lumbricus sp.) based on organoleptic, physical, and chemical tests. The treatments tested levels of substitution of fish meal with earthworms meal in artificial feed milkfish, namely: feed A (0%); feed B (34,62%); feed C (65,38%) and feed D (100%). The organoleptic and physical test showed that all the feed has a smooth texture, pungent aroma, and brown in color, with good water stability (rupture velocity ranged from 91,25±1,47 up to 92,87±1,67 minutes and dispersion of solids 11,14±1,55 up to 11,87±1,3%), hardness 84±0,18 up to 84,71±1,24%, sinking velocity 5,07±0,68 up to 5,64±0,17 cm/sec, the level of homogeneity of 81,34±0,17 up to 85,68±1,85%, the allure of 0,62±0,58 up to 0,65±0,12 cm/sec and delicious power of 0,059±0,024 up to 0,067±0,032 g/fish weight/day. The quality of feed is chemically with moisture content ranging from 8,4–9,1%, 16,7–19,46% ash, 31,07–32,37%, protein, 6,67–7,58% fat, crude fiber 7,45–7,87%, NFE (nitrogen free extracts) 35,35–35,48%. Results show that different levels of substitution of fish meal with earthworms meal (Lumbricus sp.) produces the same feed quality and contains nutrients in a range requirement milkfish. Accordingly, earthworms meal (Lumbricus sp.) can be substituted for fish meal in fish milk feed artificial up to 100%.Keywords: substitution, fish meal, earthworms meal (Lumbricus sp.), artificial feed, milkfish